Endocrine responses, weight change, and energy sparing mechanisms during Ramadan among Gambian adolescent women. Issue 3 (3rd March 2014) - Reiches, Meredith W.; Moore, Sophie E.; Prentice, Andrew M.; Ellison, Peter T.
ABSTRACT Objectives Ramadan fasting imposes a diurnal rather than a chronic energetic challenge. When Ramadan occurs during the agricultural season in subsistence populations, diurnal and chronic effects combine. The impact of layered energetic challenges on adolescent activity, metabolism, and body composition have not been quantified. This study compares the effects of a Ramadan (30 July–3 October 2009) and subsequent non‐Ramadan (14 July–12 August 2010) agricultural season in 67 Gambian subsistence agriculturalist women between 14 and 20 years old. Methods Researchers collected body composition, anthropometric, metabolic, and activity data. Metabolic hormones were measured in weekly urine (C‐peptide of insulin) and serum (leptin). Energy expenditure was estimated from heart rate calibrated for oxygen consumption. Results Participants lost more weight (Wald Chi‐square 8.7, P < 0.01) and lean mass (Wald Chi‐square 4.7, P < 0.05) in Ramadan than in the non‐Ramadan agricultural season. Energy expenditure was lower (Wald Chi‐square 11.2, P = 0.001) and there was a negative correlation between resting metabolic rate and energy expenditure in activity (R2 = 0.097, F = 5.366, P = 0.025) during Ramadan. Leptin and C‐peptide were higher during Ramadan (Wald Chi‐square 53.7, P < 0.001 and Wald Chi‐square 15.0, P < 0.001). Conclusions Even using energy sparing behaviors, adolescent women enter negative energy balance when Ramadan and the agricultural season co‐occur. Metabolic physiology shows a transient response to high glycemic index foods consumed at night. Older and larger individuals sustain greater losses during Ramadan. Am. J. Hum. Biol. 26:395–400, 2014. © 2014 Wiley Periodicals, Inc.